Effects and utility of an online forward triage tool during the SARS-CoV-2 pandemic: a mixed method study and patient perspectives, Switzerland. Issue 7 (12th July 2022) - Michel, Janet; Mettler, Annette; Stuber, Raphael; Müller, Martin; Ricklin, Meret E; Jent, Philipp; Hautz, Wolf E; Sauter, Thomas C
Abstract : Objective: To assess the effects (quantitatively) and the utility (qualitatively) of a COVID-19 online forward triage tool (OFTT) in a pandemic context. Design: A mixed method sequential explanatory study was employed. Quantitative data of all OFTT users, between 2 March 2020 and 12 May 2020, were collected. Second, qualitative data were collected through key informant interviews (n=19) to explain the quantitative findings, explore tool utility, user experience and elicit recommendations. Setting: The working group e-emergency medicine at the emergency department developed an OFTT, which was made available online. Participants: Participants included all users above the age of 18 that used the OFTT between 2 March 2020 and 12 May 2020. Intervention: An OFTT that displayed the current test recommendations of the Federal Office of Public Health on whether someone needed testing for COVID-19 or not. No diagnosis was provided. Results: In the study period, 6272 users consulted our OFTT; 40.2% (1626/4049) would have contacted a healthcare provider had the tool not existed. 560 participants consented to a follow-up survey and provided a valid email address. 31.4% (176/560) participants returned a complete follow-up questionnaire. 84.7% (149/176) followed the recommendations given. 41.5% (73/176) reported that their fear was allayed after using the tool. Qualitatively, seven overarching themes emerged namely (1) accessibility of tool, (2) user-friendliness of tool, (3) utility of tool as an information source, (4) utility of tool in allaying fear and anxiety, (5) utility of tool in medical decision-making (6) utility of tool in reducing the potential for onward transmissions and (7) utility of tool in reducing health system burden. Conclusion: Our findings demonstrated that a COVID-19 OFTT does not only reduce the health system burden but can also serve as an information source, reduce anxiety and fear, reduce potential for cross infections and facilitate medical decision-making.